Roles and Worlds in the Hybrid RPG Game of Oblivion - Champion, Erik (Hogeschool voor de Kunsten, 2009)
Role-playing is both an important part of cultural learning (Hallford and Hallford 2001 pp231-236), and an important genre in computer games (Tychsen 2006). Roles are intrinsically related to the notion of social worlds, yet exactly how is not clear in the academic literature. There are few grounded theories in computer game studies on how roleplaying works in sustaining and augmenting a thematic “world”, there are few clear descriptions of what “world” means in this context, and the social versus cultural dimensions of both roles and worlds are seldom delineated. I suggest that the cultural and social dimensions of both real world and virtual world playing are important, and that commercial computer role-playing games (CRPGs) offer more opportunities to support deeper cultural aspects of role-playing. Secondly, I wish to examine the relation of cultural identity to ownership and social purpose and how role-playing can be more fully and richly rounded out by computer-simulated game play. Thirdly, I’ll discuss features for further research agendas to improve Oblivion in particular and CRPGs in general for the gaming public, and to explore their use as vehicles for simulated purposes.